Linking Big Five Personality Domains and Facets to Alcohol (Mis)Use: A Systematic Review and Meta-Analysis. - Lui, P Priscilla; Chmielewski, Michael; Trujillo, Mayson; Morris, Joseph; Pigott, Terri D (Alcohol & Alcoholism, 2022)
Aims The goal of this investigation was to synthesize (un)published studies linking Big Five personality domains and facets to a range of alcohol use outcomes. Meta-analyses were conducted to quantify the unique associations between alcohol use outcomes and each Big Five personality domains over and above other domains. Within each domain, meta-analyses also were conducted to examine the unique contribution of each personality facet in predicting alcohol use outcomes. Methods Systematic literature reviews were performed in PsycINFO and PubMed using keywords related to alcohol use and personality. Peer-reviewed and unpublished studies were screened and coded for the meta-analyses. A total of 80 independent samples were subjected to correlated effects meta-regressions. Results Over and above other Big Five personality domains, both conscientiousness and agreeableness were negatively correlated with alcohol consumption, risky/hazardous drinking and negative drinking-related consequences. Facet-level analyses indicated that deliberation and dutifulness were uniquely associated with alcohol (mis)use over and above other conscientiousness facets, and compliance and straightforwardness were uniquely associated with alcohol (mis)use over and above other agreeableness facets. Extraversion—namely excitement seeking—was correlated with alcohol consumption, whereas neuroticism—namely impulsiveness and angry hostility—was correlated with negative drinking-related consequences. Conclusions Personality characteristics are robust correlates of alcohol (mis)use. Examining relevant narrowband traits can inform mechanisms by which personality affects drinking behaviors and related problems, and ways to enhance clinical interventions for alcohol use disorder. Gaps in this literature and future research directions are discussed.